PATCHLYFE: FASHION WEAR UPCYCLING PROGRAM DARI LIMBAH FAST FASHION PADA KAWASAN KAMPUNG MUHARTO KOTA MALANG - Aliyah, Jannatin; Ariella, Isfina; Soffi, Dewi Ariyanti (Wisesa: Jurnal Pengabdian Masyarakat, 2023)
The rapid growth of the fast fashion industry not only contributes to national income by absorbing a lot of labor but also creates waste problems which have negative impacts on the environment. Consequently, there is a need for upcycling efforts that aim to minimize waste and improve the economy of communities with low economic levels. Muharto Village, Malang City, is a densely populated area that has potential for implementing upcycling-based empowerment programs. The objectives of this research are: 1) Identify and explore the economic strength of the people of Muharto village, Malang City; and 2) Designing a long-term strategy to solve the fast fashion problems using the upcycling-patchwork method through the PATCHLYFE program. The research was conducted at RT 07 and 11, RW 06 V/B Muharto, Kotalama, Kedungkandang, Malang City. The theoretical basis used is sociopreneur theory. This research uses a mixed-method method by collecting data through questionnaires, interviews and assessing the socio-economic conditions of the Muharto area community. The research was analyzed using SWOT analysis and IE matrix followed by qualitative analysis through collecting, reducing, presenting data and drawing conclusions. From the results of this research, it was found that: 1) The economic strength of the Muharto community is relatively low, which is correlated with the low level of individual formal education and the high unemployment rate of the productive age population; and 2) PATCHLYFE as an empowerment strategy to utilize fast fashion waste through upcycling methods, holding disciplined training to increase the community's internal skills, and motivation so that empowerment can be carried out in a sustainable manner, collaborating with local government institutions, and providing programs that do not require difficult transportation. PATCHLYFE program is designed to consist of three stages: preparation, implementation, monitoring and evaluation.